Melting down: Systemic financial instability and the macroeconomy - Philipp Hartmann; Kirstin Hubrich; Manfred Kremer; Robert J. Tetlow (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We integrate systemic financial instability in an empirical macroeconomic model for the euro area. We find that at times of widespread financial instability the macroeconomy functions fundamentally differently from tranquil times. We employ a richly specified Markov-Switching Vectorautoregression model to capture the dynamic relationships between a set of core macroeconomic variables and a novel indicator of systemic financial stress. Both the parameters that capture the transmission of shocks through the economy and the variances of the shocks change at times of high stress in the financial system. In particular, the negative output effects of sizeable increases in financial stress are much larger after such a regime change than during tranquil times. Macroprudential and monetary policy makers are well advised to take these nonlinearities into account.
Keywords: E44; C11; C32; 330